USABILITY TESTING ON POTWIS APPLICATIONS - Yuliyana, Tifani; Arthana, I Ketut Resika; Agustini, Ketut (JST (Jurnal Sains dan Teknologi), 2019)
This research was conducted to evaluate POTWIS application by highlighting three usability concepts that effectiveness, efficiency, and the satisfaction of the user in using POTWIS application measured by usability testing methode, Performance Measurement, RTA, UEQ, and SUS technique. The purpose is to know the result of usability testing and improvement recommendation on POTWIS application based of the result of usability testing.The result of this research is based on analysis of statical calculation Mann Whitney U Test, UEQ dan SUS which showed (1) POTWIS application is not effective seen from the existance of the mistake made by respondent during the task, (2) POTWIS application is efficient seen from the time of task execution because the execution time between proficient group and beginner group was not significantly different, (3) POTWIS application has not met the scale of efficiency measured by UEQ with score 0.625 which showed below the average and (4) POTWIS application has not fulfilled user satisfaction measured by SUS with score 53.00 which is stated still below the average score is > 68.